Evaluasi Kinerja Sistem Informasi Akuntansi Terhadap Pengambilan Keputusan Pada Laporan Keuangan - Siti Ambar Mukti Puji Lestari; Allesia Putri Wijaya Sutikno; Irda Agustin Kustiwi (Pusat Riset dan Inovasi Nasional, 2024)
One of the important things in a company is its accounting system, where accounting is an information system that records, identifies, communicates and collects financial data that is useful in decision making. Through the existence of technology that continues to develop in each era, the availability of information systems has added value to processes, production, quality, management, decision making and problem solving as well as competitive advantages that will be beneficial for business activities. This research uses qualitative research methods with a descriptive approach. The type of data used is secondary data with a library study data collection method. The results of this research found that other studies showed similar results, namely that the performance of the accounting information system had an influence on decision making in financial reports.